The role of product diversification in enhancing market vendor adaptability and food-system resilience in Senegal, West Africa - Muriithi, Cyrus K; Chege, Christine Kiria; Ouedraogo, Issa; Mwongera, Caroline (Elsevier BV, 2026)
Severe food insecurity in Senegal, exacerbated by climate shocks and weak infrastructure, underscores the need to understand the role of market vendors in food system resilience. Unlike producers, vendors remain understudied despite their central role in food access. This mixed-methods study examines how product diversity, measured using the Shannon-Wiener index, influences Market Vendor Adaptive Capacity (MVAC) among 691 vendors in Sedhiou and Tambacounda. Survey and interview data reveal that diversity enhances MVAC, particularly for small retail and open-air vendors offering both staple foods and nutrient-rich products. Vendor characteristics such as employing staff, extending credit, and participating in training further strengthen adaptability, while systemic constraints like poor infrastructure and high transport costs limit benefits, especially in rural areas. Results indicate that diversity functions less as an independent driver and more as a strategic outcome of vendor capacity, reframing its role within resilience theory. The study contributes by (1) linking product diversity to adaptive capacity, (2) identifying enabling and constraining factors, and (3) outlining policy directions, including infrastructure investment, financial support, and vendor training. Strengthening these areas can expand food access, bolster resilience, and advance Sustainable Development Goal 2 (Zero Hunger) in Senegal with implication for West Africa.